Fiscal policy under a minimum‐time objective. (21st November 2017) - Dai, Darong
Abstract: In an endogenous growth model, we characterize the fiscal policy driven by a minimum‐time objective of economic development. We find that in equilibrium government should levy the highest possible consumption taxes, reduce public expenditures to the lowest possible level, and keep labor income tax rate and capital income tax rate satisfy a substitution relationship at the balanced budget constraint. We also identify the condition under which income tax rate should be set to zero. We further find that the equilibrium fiscal policy is equivalent to the growth‐maximizing fiscal policy, whereas it generally deviates from the welfare‐maximizing fiscal policy. We hence identify a circumstance where setting the policy goal of reaching an economic‐performance target as soon as possible cannot be justified in the sense of maximizing the welfare of households.